Key factors influencing the professional development of golfers in South Africa: a reflexive thematic analysis - Stephanus Johannes Roos; Julius Jooste; Ankebé Kruger (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background An estimated 61.2 million adults play golf worldwide, with approximately 139,000 golfers affiliated with clubs in South Africa. Despite golf’s popularity as a recreational activity, the path to professional status and its sustainment is reserved for a few who demonstrate exceptional skill and dedication. Recognising the existing gap in research regarding the developmental trajectory of tour professional golfers in South Africa, there is an increasing need to identify the key factors that promote their professional development in this unique context. This study addressed this gap by aiming to elucidate the key factors contributing to their development. Methods The study employed a qualitative descriptive design using semi-structured interviews with a purposeful sample (N = 17) of male and female tour professional golfers ranked within the top 100 on the Sunshine Tour and Professional Golfers Association of South Africa (PGASA) teaching professionals. Results Reflexive thematic analysis identified nine overarching themes as key factors contributing to professional development in golf, namely a supportive developmental environment, competition-specific training, career management, a team of professional staff, financial resources, physical conditioning, lifestyle habits, psychological and physiological proficiency, and course management. Conclusion This study’s findings may inform the development of a golf-specific framework for professional development tailored to a holistic approach in preparing golfers for professional advancement, highlighting its potential to optimise performance outcomes.